De La Salle University alumni office lost facsimile machine - Alumni Office-De La Salle University, Manila (Animo Repository, 1991)
The facsimile machine of the De La Salle University (DLSU) Alumni Office was stolen during the July 18 Welga ng Bayan suspension of classes.